Odpowiedzi

Najlepsza Odpowiedź!
2010-01-17T19:48:52+01:00
A) x+2y=-13 |*(-1)
-x-2y =13

b) 3x+y=-5 |*(-2)
-6x-2y=10

c) -x+4y=2 |*(-½)
½x-2y=-1
1 3 1
2010-01-17T19:49:20+01:00
A) x+2y=-13 |x(-1)
-x-2y=13

b) 3x+y=-5 |x(-2)
-6x-2y=10

c) -x+4y=2 |:(-2)
0,5x-2y=-1
2010-01-17T19:51:07+01:00
Pomnóż obie strony równania przez taką liczbę , aby współczynnik przy zmiennej y był równy -2.
a) x+2y=-13
b) 3x+y=-5
c) -x+4y=2

a)
x + 2y = -13 / * (-1)
-x - 2y = 13

b)
3x + y = -5 / * (-2)
-6x - 2y = 10

c)
-x + 4y = 2 / * (-½)
½x - 2y = -1